Finite-difference time-domain method calculation of light propagation through H-PDLC - Kubytskyi, V.; Reshetnyak, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Presented is the study of the diffraction properties of transmission holographic
polymer dispersed liquid crystal (H-PDLC) grating. We constructed a two-dimensional
model of H-PDLC film with cylindrical LC droplets. Director distribution inside LC
droplets was calculated using the Monte-Carlo method. To calculate light propagation
through the film we have solved numerically the Maxwell equations using the finitedifference time-domain method (FDTD). The FDTD analysis of diffraction was
performed for s- and p-polarized incident light. Externally applied electric field influence
on the diffraction efficiency was studied.